The Concept of Faith in the Letter of James: A Discourse Analysis on James 1-2 - Chandra Gunawan (Verbum Christi: Jurnal Teologi Reformed Injili, 2016)
James' teaching about faith has been downplayed for so many years. Since the concept of faith in the NT has been read mainly in light of Paul's theology, scholars ignores James? teaching on faith, which has different emphasis from Paul. Biblical scholars and theologians have tried to solve the tension between Paul's teaching about faith and James'. While historical approach applied to deal with this issue has lead NT scholarship to enless debate, this study proposes that the Letter of James was not sent to handle problems that occur because of Paul. This essay uses discourse analysis to understand how the the concept of faith in James 1 and 2 should be grasped. This work finds that James addresses his letter to pastoral believers? community and help them to understand sufferings in their lives. James emphasizes that faith is not only a confession but also a commitment to live in accordance with the true belief.